Socio-legal study on knowledge of respondents in Malaysia: an empirical evidence from the registration of cross-border marriage - Abdul Hak, Nora; Md Said, Muhamad Helmi; Md Hashim, Noraini; Che Soh @ Yusoff, Roslina (UPM Press, Universiti Putra Malaysia, 2017)
Cross-border marriage is a marriage without the permission from the marriage registrar in each state and the solemnisation is either contracted in Malaysia or outside Malaysia. This type of marriage violates the purpose of marriage which is to obtain peace and tranquillity. The purpose of this study is to examine and analyse the level of knowledge among the respondents towards the registration of cross-border marriage among Muslims in Malaysia. The sample consists of 400 respondents from four regions in Malaysia. A questionnaire survey was the main data collection method employed in this study and further supported by semi-structured interview. Based on the findings, the respondents are already aware of the opportunity to register the marriage at the court. Despite their acknowledgement, new regulation and policy to control cross-border marriage should be implemented in order to curb the issue from worsening in the future.